Delegated and implementing acts - Craig, P (Oxford University Press, 2018)
The Lisbon Treaty created the dichotomy between delegated and implementing acts in Articles 290 and 291 TFEU, having taken over the core assumptions in this regard from the Constitutional Treaty. The chapter begins by considering the core assumptions underlying the Lisbon model and the rationale for the division between the two species of secondary acts. The subsequent analysis then addresses the tensions and strains in the application of this divide in the years since the Lisbon Treaty was ratified.